Information, attention, and decision making: From the Editors - VAN KNIPPENBERG, Daan (Institutional Knowledge at Singapore Management University, 2015)
More than five decades after the seminal works on how individuals process information and make decisions within organizations were published (Cyert & March, 1963; Simon, 1957), the thesis that individuals, groups, and organizations are bounded in their rationality and ability to attend to information continues to remain salient. Individuals and organizations display cognitive and motivational biases, both in their attention to information and in their decisions based on that information (De Dreu, Nijstad, & van Knippenberg, 2008; Ocasio, 2011; Tversky & Kahneman, 1974). The nature and volume of information, and managers’ behaviors in seeking and using information, have undergone massive transformation over these past 50 years, which have seen the emergence of electronics, computers, and the Internet. Advances in information technology, mobile communications, and big data collection and storage mean that more people and firms have access to more information than ever before (George, Haas, & Pentland, 2014; Hilbert & López, 2011). Yet, our frameworks of attention and decision making have not seen corresponding radical shifts. Perhaps, the underlying processes of decision making remain the same despite the transformative change in context. Alternatively, it is plausible that our theoretical advances have not matched the speed of change in information contexts confronted by businesses and policymakers alike.